(untitled) (Proceedings of International Educators Conference, 2023)
This article delves into the ontophylogeny of human organs, exploring the evolutionary development of vital structures in the human body. Through a multidisciplinary approach encompassing phylogenetics, comparative anatomy, and embryonic development, the study aims to unravel the intricate evolutionary history of human organs. By examining the similarities and differences across species and tracing the developmental trajectories during embryogenesis, we seek to elucidate the underlying principles that have shaped the architecture of the human body.